A new de novo SYT2 mutation presenting as distal weakness. Neuropathy or neuromuscular junction dysfunction?. Issue 1 (22nd December 2020) - Fionda, Laura; Turon‐Sans, Janina; Fuentes Prior, Pablo; Bernal Noguera, Sara; Cortés‐Vicente, Elena; López‐Pérez, Maria Angeles; Gallardo, Eduard; Rojas‐García, Ricard
Abstract: We report the case of a patient with a clinical phenotype characterized by distal lower limb weakness and pes cavus. The electrophysiological study showed slightly reduced or normal amplitude of motor potentials, a decremental response to repetitive nerve stimulation and post‐exercise facilitation. Muscle biopsy showed only mild neurogenic features. Genetic analysis included a clinical exome sequencing, followed by Sanger analysis. Three‐dimensional (3D) models were generated with a SwissModel (https://swissmodel.expasy.org/ ) to explain the clinical observations and reinforce the pathogenic nature of the genetic variant identified. Genetic analysis demonstrated a new de novo heterozygous in frame deletion of the SYT2 gene (NM_177402.4: c.1082_1096del), confirmed by Sanger sequencing, which removes five aminoacids in the C2B domain of synaptotagmin‐2 protein, that cause a profound effect on the structure and function of this synaptic vesicle protein. We identified a de novo genetic variant in the SYT2 gene, further supporting its association with a highly stereotyped clinical and electrophysiological phenotype. Our case showed electrophysiological features consistent with a presynaptic dysfunction in the neuromuscular junction with normal post‐exercise amplitudes, not supporting the presence of predominant axonal damage. Although the analysis of SYT2 gene should be included in genetic analysis of patients presenting with this clinical phenotype that mimics motor neuropathy, clinicians have to consider the study of neuromuscular transmission to early identify this potentially treatable condition.